The 2016 National Emerging Leadership Summit : From “Professionals Leading Passionate Innovation” to “Advancing Our Profession, Enhancing Lives” - Jackson, Luke; Hansen, Kevin E.; Olson, Douglas M. (My University, 2018)
By 2050, the number of Americans aged 65 and older is projected to nearly double to 83.7 million. 1 About 40% of nursing home administrators (NHA) are 55 and older, and 32% of NHAs are expected to retire in the next 10 years. 2 The past years of the National Emerging Leadership Summit (NELS) for Healthcare Administrators in Health and Aging Services participants have defined challenges for the NHA profession, including recruitment and perception issues, due to low pay and negative public perceptions. NELS is an annual gathering of emerging leaders in the field of health and aging services administration to engage in discussions of current best practices, meet with representatives of key professional organizations, gain an inside perspective on the legislative process, and explore solutions for attracting and retaining new and evolving leaders. The first NELS cohort in 2010 built the foundation for all future NELS participants by identifying four thematic areas, which have evolved throughout the seven-year life of NELS.
Color poster with text, charts, and graphs.
Keywords: Leadership; Health services administrators; Health services administration; Posters